Edukasi Manajemen Perawatan Luka Perineum Pada Ibu Nifas Hari Ke 7 Di Klinik Pratama Kota Medan Tahun 2022 - Alisarjuni Padang; Rados Kristian; Ovi Krisna Ndraha; Fahira Annisa Fitri; Widya Jerni Gulo (Universitas Muhammadiyah Manado, 2022)
This community service aims to enhance knowledge and skills in perineal wound care for postpartum mothers on the seventh day at the Primary Clinic in Medan City in the year 2022. Through seminars and training sessions, our efforts are directed towards providing relevant information on perineal wound care, explaining signs of infection, and instructing proper care techniques. It is anticipated that this intervention will yield positive benefits for postpartum mothers, elevate the quality of perineal wound care, and overall, support endeavors in preventing post-delivery complications. Postpartum infections, such as sepsis, remain a leading cause of maternal mortality in developing countries.